GLOBALIZATION IN THE MODERN THEORETICAL DISCOURSE: FROM PLURALISM TO INTERDISCIPLINARITY - E. A. Avdeev (Гуманитарные и юридические исследования)
The article deals with different types of theoretical concepts of globalization. It is argued that all theories reduce real diversity of globalization forms to one or more aspects. The author concludes that interpretation of globalization as part of the non-classical social cognition has methodological prospects.